Thoughts and after thoughts - Gauhar, Altaf, 1923- (Lahore : Sang-e-Meel Publications, 1998)
Collection of articles previously published in a Daily "The Nation" during 1995-1998.
Keywords: Pakistan -- Politics and government -- 1971-1988.; Pakistan -- Politics and government -- 1988-